Two new species of subgenus Tripodura Towns (Diptera, Chironomidae, Polypedilum) from Oriental China - Chen, Jinxian; Zhang, Ruilei (Zootaxa, 2021)
P. (T.) anningense sp. n. and P. (T.) biloborum sp. n. are described and illustrated as male imagines from Oriental China. DNA barcodes of two new species are also presented. A key to known male imagines of the subgenus Tripodura from China is given.